Feeding holy bodies: A study on the social meanings of a vegetarian diet to Seventh-day Adventist church pioneers - Ruben Sánchez; Ramon Gelabert; Yasna Badilla; Carlos Del Valle (HTS Teologiese Studies/Theological Studies, 2016)
Ten years ago National Geographic magazine reported that the Loma Linda Seventh-day Adventist population is one of the communities in the world that lives longer and with a higher quality of life thanks in part to the biological benefits of a vegetarian diet. Along with National Geographic, other media outlets have reported since then that the Adventist religious community considers a plant-based diet a very important factor for a healthy lifestyle. Adventists have been promoting this type of diet worldwide for more than 150 years. This article is an attempt to understand from a social-scientific perspective the origin of the importance they lend to diet and see whether this helps explain why approximately 150 years after the founding of the church, diet remains crucial for Adventists around the world. The conclusion proposed is that Adventists understood the adoption of a plant-based diet as a special divine instruction in order to nourish their new identity as a special people differentiated from the rest of society. This was possible through a desecularisation of diet that placed food in the moral category of the Adventist belief system.